Taxonomic notes and a new species of Episcepsis Butler, 1877 (Lepidoptera, Erebidae, Arctiinae, Arctiini, Ctenuchina) - Pinheiro, Lívia R.; Junior, Elias C. Araujo (Zootaxa, 2017)
Taxonomic notes and the description of a new species of Episcepsis are provided. The synonymization of Episcepsis aelia Schaus, 1889, from Mexico, under E. venata Butler, 1877, from the Brazilian Amazons, is revised. Genital morphology of males and females has shown the validity of E. aelia revis. stat. Additionally, the discovery of specimens from the Brazilian Atlantic Forest externally indistinguishable from both E. venata and E. aelia has led to the description of E. atlantica sp. nov. Finally, the following new combinations in Episcepsis are proposed: E. fumata (Rothschild), comb. nov., and E. coeruleocephala (Rothschild), comb. nov.